Extending hybrid SQL/NoSQL database by introducing statement rewriting component - Bjeladinovic, Srdja (Computer Science and Information Systems, 2025)
Contemporary organisations often include different business subdomains, for which it is neither easy nor optimal to decide on using an exclusive database type. The hybrid SQL/NoSQL databases encompass various types of databases unified into a unique logical database. At the same time, they provide the usage benefits of working with the SQL and the NoSQL databases simultaneously. Recently, there has been an increase in research that deals with the challenges of hybrid databases? query optimisation, especially query rewriting. This trend opened up possibilities for analysing the influence of applying different statement rewriting techniques to other data manipulation statements besides queries (i.e. INSERT, UPDATE and DELETE) and its impact on the average execution times. In this paper, a process model for applying automatic hybrid statements? rewriting was designed, and the architecture for the hybrid database was extended with the newly developed Statement Rewriting Component (SRC). The tested use cases were conducted on the example of Oracle/MongoDB/Cassandra hybrid before and after introducing SRC. The tests have shown particular decreases in the average execution times of the system with the SRC.